The effect of surgery report cards on improving radical prostatectomy quality: the SuRep study protocol - Breau, R. H; Kumar, R. M; Lavallee, L. T; Cagiannos, I.; Morash, C.; Horrigan, M.; Cnossen, S.; Mallick, R.; Stacey, D.; Fung-Kee-Fung, M.; Morash, R.; Smylie, J.; et al. (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background The goal of radical prostatectomy is to achieve the optimal balance between complete cancer removal and preserving a patient’s urinary and sexual function. Performing a wider excision of peri-prostatic tissue helps achieve negative surgical margins, but can compromise urinary and sexual function. Alternatively, sparing peri-prostatic tissue to maintain functional outcomes may result in an increased risk of cancer recurrence. The objective of this study is to determine the effect of providing surgeons with detailed information about their patient outcomes through a surgical report card. Methods We propose a prospective cohort quasi-experimental study. The intervention is the provision of feedback to prostate cancer surgeons via surgical report cards. These report cards will be distributed every 3 months by email and will present surgeons with detailed information, including urinary function, erectile function, and surgical margin outcomes of their patients compared to patients treated by other de-identified surgeons in the study. For the first 12 months of the study, pre-operative, 6-month, and 12-month patient data will be collected but there will be no report cards distributed to surgeons. This will form the pre-feedback cohort. After the pre-feedback cohort has completed accrual, surgeons will receive quarterly report cards. Patients treated after the provision of report cards will comprise the post-feedback cohort. The primary comparison will be post-operative function of the pre-feedback cohort vs. post-feedback cohort. The secondary comparison will be the proportion of patients with positive surgical margins in the two cohorts. Outcomes will be stratified or case-mix adjusted, as appropriate. Assuming a baseline potency of 20% and a baseline continence of 70%, 292 patients will be required for 80% power at an alpha of 5% to detect a 10% improvement in functional outcomes. Assuming 30% of patients may be lost to follow-up, a minimum sample size of 210 patients is required in the pre-feedback cohort and 210 patients in the post-feedback cohort. Discussion The findings from this study will have an immediate impact on surgeon self-evaluation and we hypothesize surgical report cards will result in improved overall outcomes of men treated with radical prostatectomy.